MATERIAL FORCE, DIALECTIC EVOLUTION AND THE ROLE OF ACTION IN CHINESE PHILOSOPHY: WANG FUZHI'S NEO-CONFUCIAN VIEW. - VEREȘ, Diana-Elena (Studii de Ştiintă şi Cultură, 2024)
The transition from the Ming Dynasty to the Qing Dynasty of Manchurian origin brought with it a series of major changes, not only from a political perspective but also from a cultural and philosophical perspective. Wang Fuzhi (1619-1692), a Chinese philosopher and fervent patriot, fighting against the Manchurian invasion, contributes to the creation of Chinese ethnic thought, highlighting through his works the importance of human action as a decisive factor in the nation's destiny. The article analyzes Wang Fuzhi's contribution to Neo-Confucian philosophy in the 17th century and aims to highlight key concepts from the vision of this Chinese thinker, ideas that can provide a better understanding of Chinese philosophy.